Lawmen : Bass Reeves [videorecording (DVD)] - Feehan, Chad, 1978- (Paramount, 2024)
It follows the journey of Reeves and his rise from enslavement to law enforcement as one of the first Black U.S. Deputy Marshals west of the Mississippi. Despite arresting over 3,000 outlaws during his career, the weight of the badge was heavy, and he wrestled with its moral and spiritual cost to his beloved family. This release features over two hours of special features, including an exclusive interview with Production Designer, Wynn Thomas (Malcolm X, Hidden Figures).